Chronic Pain After Surgery: A Growing Reality - Rivotti Appleton, Sofia (Journal of the Portuguese Society of Anesthesiology, 2018)
Despite the advance in technology and health, and although currently being considered the fifth vital sign, pain does not cease to be subjective, and therefore underestimated and under treated. With implications in so many diseases, pain treatment should be a priority and the prevention of chronicity, our concern. Only in this way we could reduce the co-morbidities associated with the treatment and its associated costs. This work aims to highlight the incidence of chronic pain after surgery so that the magnitude of the problem becomes more visible. A literature search was carried out on PubMed using the keywords "chronic pain after surgery", "chronic pain after surgery epidemiology ", "costs associated to chronic pain". It was given preference to articles published in the last 5 years and still added articles with scientific interest for your novelty or impact in the area. Chronic post surgical pain, defined as "a pain that arises after surgery and that lasts at least 2 months", has a variable incidence, but growing, as the number of surgeries increases annually and may be associated with major surgery, as the surgery less invasive. The reported incidence of chronic pain after major surgery is between 20% - 50%, and in less invasive surgeries such as repair of inguinal hernia or cesarean section, the incidence of chronic pain after surgery was around 10%. If we think that the incidence of chronic pain after surgery is approximately 10%, and if in Portugal approximately 900 000 major surgeries are performed, 90 000 patients may experience chronic pain.It is, however, a painful syndrome still overlooked and underappreciated, with repercussions on the daily life of many patients and costs associated with an overload for the National Health System.